PRICING RESIDENTIAL REAL ESTATE IN URBAN AREAS OF KAZAKHSTAN - Makishev, Dauren; Akhmet, Alisher (Nazarbayev University Graduate School of Business, 2023)
Real estate market is the basis of any economy in the world, as housing in this case is one of the most important or rather basic needs for any human in the world. Proceeding with the analysis of the real estate market with the thorough empirical study is usually made with a precaution of a classical idea and scheme - introducing relevant or classical problem/topic, looking at the researches done by other authors in previous years regarding this topic, explaining and expanding on the data used in the paper/article/research with further discussion of methodology, results and conclusions with possible evaluation and implications beforehand. However, this research as primitive and timeless its topic seems to be except for the use of the relevant methodologies and filling necessary gaps in existing literature about real estate pricing in Kazakhstan is not aimed at not just writing another empirical paper - but making a paper that will be worth thinking upon, promoting further research and delving not only in empirical reasonings behind the real estate market pricing used in other works - but looking at the concept of real estate as a full with some historical remarks and notes, that may be useful and can be discussed as well...
Keywords: type of access: gated access